SHORELINE CHANGES ALONG PART OF THE COASTAL ZONE OF PIERIA AND ASSESSMENT OF THE FUTURE SEA-LEVEL RISE IMPACTS - ΤΣΑΝΑΚΑΣ, Κ.; ΚΑΡΥΜΠΑΛΗΣ, Ε.; ΠΑΡΧΑΡΙΔΗΣ, Ι. (Bulletin of the Geological Society of Greece, 2005)
The aim of this study is to detect shoreline changes along part of the coastal zone of Piena during the time period between 1969 and 2000 using aerial photographs and satellite images. Additionally, a quantitative and qualitative assessment of the future sea-level rise (triggered by the global climate change) implications to the physical and socioeconomic environment of the area is attempted taking into account various sea-level rise scenarios. Retreating as well as prograding regions along the study area were defined and retreating/prograding rates for the time periods 1969-1987 and 1987-2000 were estimated using GIS and Remote Sensing techniques. Building activity rates for the coastal area of Paralia Katerinis were also estimated for the same periods. The coastline of the study area is retreating^ except than the area north of torrent Mavroneri where a progradation rate of 48 cm/year was estimated between 1969 and 1987. Retreating rate of the coast for the northern part of the area (Saltworks) is estimated to be 25 cm/year and 19 cm/yrear for the periods of 1969-1987 and 1987-2000 respectively. The broader study area is particularly vulnerable to a potential future sealevel rise due to the low-lying topography of the coastal zone and intensive socioeconomic activities such as tourism and commerce.